Degrading Superiority Domination with Break and Build Method for Staff Working Independence Training - Pamuji, Wirawan; Lili Dahliani (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Superiority at Company counts the most arbitrary domination to manage its regulation towards working performance. The Research applies Descriptive Qualitative Methods in trainingdeveloping Domain of reducing superiority domination about controlling staffs at company with subjectivity pattern in training performance of staffs in declining actual and potential skills rather than persuading close relationship between manager and subordinates. Due that contextualized method training Independence Performance at company for staffs are not intended to disrespect manager but it is adherent to standardized operation to gain company quality with not merely admitted for leadership protocol by analyzing problems and solution from staffs called Break and Build Method